2008
DOI: 10.1002/j.2048-7940.2008.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

A Telerehabilitation Model for Victims of Polytrauma

Abstract: The Low Activities of Daily Living Monitoring Program (LAMP) at the North Florida/South Georgia Veterans Health System is a telerehabilitation program that promotes independence for veterans experiencing difficulties with activities of daily living by focusing on a combination of care coordination, assistive technology/adaptive equipment, and home environmental modifications. Initially designed to serve elders at risk of institutionalization, LAMP now is being adapted to the needs of veterans living with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…They also support the transmission and sharing of critical components (vs. a large volume of data with minimal value added). Integrated systems will also be needed to address the complex needs associated with new and multifaceted disability such as polytrauma in veterans, which presents needs as diverse as case management, assistive technology, and home modification (Bendixen, Levy, Lutz, Horn, and Chronister, 2008). In addition, the field of robotics is now being applied to rehabilitation applications, offering opportunities to integrate haptic or visual responses with artificial intelligence and high data storage capacity (Brewer, McDowell, & Worthen-Chaudhari, 2007; Carnigan & Krebs, 2006).…”
Section: Overview Of Telerehabilitation Technologiesmentioning
confidence: 99%
“…They also support the transmission and sharing of critical components (vs. a large volume of data with minimal value added). Integrated systems will also be needed to address the complex needs associated with new and multifaceted disability such as polytrauma in veterans, which presents needs as diverse as case management, assistive technology, and home modification (Bendixen, Levy, Lutz, Horn, and Chronister, 2008). In addition, the field of robotics is now being applied to rehabilitation applications, offering opportunities to integrate haptic or visual responses with artificial intelligence and high data storage capacity (Brewer, McDowell, & Worthen-Chaudhari, 2007; Carnigan & Krebs, 2006).…”
Section: Overview Of Telerehabilitation Technologiesmentioning
confidence: 99%
“…Telerehabilitation has been evaluated widely in literature and was found to be feasible and effective in various neurological conditions including stroke (Chumbler et al, 2012;Johansson and Wild, 2011;Legg and Langhorne, 2004;Perry et al, 2011), Parkinson's disease (Giansanti et al, 2008) and other non-neurological conditions such as musculoskeletal conditions (Russell et al, 2011;Tousignant et al, 2011), injuries (Bendixen et al, 2008;Forducey et al, 2003;Houlihan et al, 2011) and chronic diseases (Steel et al, 2011). A systematic review analysing telerehabilitation therapies in stroke survivors showed positive outcomes, with a reduction in the risk of deterioration, improved ability to perform activities of daily living, reduced costs and duration of rehabilitation (Legg and Langhorne, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10] In stroke patients, telerehabilitation helped to improve their ability to do daily works and reduced costs and the duration of rehabilitation programs. 11 Although the effectiveness of telerehabilitation interventions has been investigated in the treatment of stroke, [12][13][14] Parkinson's disease, 15 musculoskeletal disorders, 16,17 injuries and lesions, [18][19][20] and chronic diseases, 21 it is not clear how using this technology is effective compared with using traditional rehabilitation for therapeutic purposes in the elderly. Therefore, the present study aimed to answer the following research question: how effective are telerehabilitation interventions compared with traditional rehabilitation services for therapeutic purposes in the elderly.…”
Section: Introductionmentioning
confidence: 99%